2014
DOI: 10.1137/120883001
|View full text |Cite
|
Sign up to set email alerts
|

Contraction Analysis for a Class of NonDifferentiable Systems with Applications to Stability and Network Synchronization

Abstract: In this paper we extend to a generic class of piecewise smooth dynamical systems a fundamental tool for the analysis of convergence of smooth dynamical systems: contraction theory. We focus on switched nondifferentiable systems satisfying Carathéodory conditions for the existence and uniqueness of a solution. After generalizing the classical definition of contraction to this class of dynamical systems, we give sufficient conditions for global convergence of their trajectories. The theoretical results are then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2
1

Relationship

5
1

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…As a representative example, we consider a network of time-switched systems of the form [44] As shown in Fig.12.6, the theoretical predictions are confirmed by the numerical simulations obtained considering T = 2 and random initial conditions.…”
Section: Recent Extensionssupporting
confidence: 56%
See 1 more Smart Citation
“…As a representative example, we consider a network of time-switched systems of the form [44] As shown in Fig.12.6, the theoretical predictions are confirmed by the numerical simulations obtained considering T = 2 and random initial conditions.…”
Section: Recent Extensionssupporting
confidence: 56%
“…Specifically, contraction of Carathéodory systems was discussed in [44]. It was shown that the switched system of interest is contracting if a unique matrix measure exists such that each of the system modes is contracting.…”
Section: Recent Extensionsmentioning
confidence: 99%
“…To illustrate the strategies presented above we use an example adapted from [14]. Specifically, we consider a switched (or blinking) network of the forṁ…”
Section: Networkmentioning
confidence: 99%
“…x m . Following similar arguments in [13], [14], the problem of proving convergence of network (8) is equivalent to that of guaranteeing that the following linear systems:…”
Section: Networkmentioning
confidence: 99%
See 1 more Smart Citation